THE GEESE MARKET IN POLAND - Katarzyna Utnik-Banaś; Janusz Żmija (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the study was to show changes in the volume of production, foreign trade and theprices of geese in Poland against the backdrop of world production, along with the presentation of newtrends. The most important producer of geese in the world was China, whose production reached 95% ofworld production in recent years. Poland remains second in the ranking (with the production of approx.30,996 tons, which accounted for 1.2% of world production in 2016), and is followed by countries suchas Egypt (1.06%) and Hungary (1.02%). Prices of goose meat were the highest of all poultry speciesand, compared to chickens, they were higher, ranging from 60% in 2005 to 170% in 2017. In Poland,production was export-oriented. Starting from 2012, interest in goose meat on the domestic market hasincreased, and consumption reached a level of 40% in the period between 2012-2013. Production in thecoming years will probably increase due to the advantages of goose meat, as well as due to the acquisitionof extremely valued down and feathers.